Flow cytometry for assessment of the tumor microenvironment in pediatric Hodgkin lymphoma - Henry, Meret (Pediatr Blood Cancer, 2018)
BACKGROUND: The role of flow cytometry in diagnosis and management of Hodgkin lymphoma (HL) remains limited. As knowledge emerges of the tumor microenvironment in this disease, various methods are being evaluated in its study. This study examines the microenvironment using flow cytometry to assess differences between subtypes and clinicopathologic correlates. PROCEDURE: A retrospective cross-sectional study was performed analyzing the tumor immunophenotype, by flow cytometry, for 31 children with classical HL. Correlation was made with patient information, including outcome. RESULTS: The makeup of the tumor microenvironment varies across subtype of HL, with T cells predominating in nodular sclerosis (NS), and similar proportions of B and T cells in mixed cellularity (MC). CD4 cells predominate in NS, whereas CD8 more so in MC subtype. The rate of continuous complete remission is significantly higher in the MC subgroup. Last, the proportion of HLA-DR/CD38 copositive lymphocytes was an independent prognostic factor for relapse/refractoriness. CONCLUSIONS: This study indicates that flow cytometry can be used to examine the tumor microenvironment in HL and that percentage of HLA-DR/CD38 copositive lymphocytes may be a biomarker for relapse and refractoriness in pediatric HL.